THE EFFECT OF PRODUCT VARIANT AND PRICE ON PURCHASING DECISIONS FOR HNI-HPAI PRODUCTS AT THE KHAIRA ISLAMIC HEALTHY HOME MEDICINE CLINIC IN BANGKINANG CITY - Fatmiwati Fatmiwati; Zulher Zulher; Sri Mulyani (STIE Bangkinang Publishing, 2020)
Research to determine the effect of product variant and price with simulthan and partial on purchasing decisions for HNI-HPAI products at the Khaira Islamic Healthy Home Medicine Clinic in Bangkinang City. The population in this study were all consumers at the Khaira Islamic Healthy Home Medicine Clinic in Bangkinang City in 2019, amounting to 1.244 consumers and based on the Slovin formula it is know that the number of samples in this study is 100 consumers at the Khaira Islamic Healthy Home Medicine Clinic in Bangkinang City. The sample collection technique is using accidental sampling technique. Data analysis was performed using multiple linear regression models. Based on the simulthan and partial test results, the variable of product variant and price have a significant effect on purchasing decisions for HNI-HPAI products at the Khaira Islamic Healthy Home Medicine Clinic in Bangkinang City. The closeness of the relationship that occurs between the atractiveness of product and price on purchasing decisions at the Khaira Islamic Healthy Home Medicine Clinic in Bangkinang City is very strong with a correlation coefficient R of 87,3%. While contribution the variable of product variant and price to the purchasing decisions variables is equual to 75,7% while the remaining 24,3% is influenced by other variables not examined in this study.